Green finance, environmental taxation, and green innovation: unraveling their influence on the growth- quality nexus in China—a provincial perspective - Md Qamruzzaman (Environmental Research Communications)
China’s fast industrialization and urbanization have led to impressive economic growth and caused severe environmental degradation, resulting in increased CO2 emissions. These emissions have increased by leaps and bounds with China’s rapid industrialization and urbanization. The case for sustainable development is compelling and has unleashed a search for green investments and technological innovations to meet the challenge. This study is motivated by the significant need to understand the effects of green finance, technological innovations, and environmental taxes on China’s economic growth and environmental sustainability. Furthermore, it tries to investigate how these elements may help make the model more sustainable and not endanger the developmental achievements of the country. For this purpose, we employed a comprehensive econometric approach through longitudinal data, and different models included Two-step GMM, Two-step system-GMM, and CS-ARDL. These methodologies portray various ways green investments, green technological innovation, tax, urbanization, inflows of FDI, and industrial structure intersect to influence environmental and economic outcomes in China. The results reflect a strong negative correlation with green investments made with CO2 emissions, proving that high investments in green technologies and practices effectively reduce carbon outputs. The study also underlined regional disparities and technological innovations in green. The study, therefore, recommends more efforts by Chinese policymakers on green finance and investment, standardization, and the rise in environmental standards across the country; enhanced efforts in further bringing down CO2 emissions through ecological taxes and incentives; and collective efforts with strong governmental support for research and development in low-carbon technologies that can help place China on a sustainable economic path.